Effect of copper, zinc and potassium phosphites on the mycelium growth of phytophthora nicotianae in olive tree dry branch disease - Lucero, Gabriela Susana (2014)
The genus Phytophthora is one of the most popular in plant pathology, because of the importance of the diseases it causes. In olive trees severe damages are caused by the disease known as “dry branch”. Recently, our work team has identified as responsible of this disease the pathogens Phytophthora palmivora, P. nicotianae and P. citrophthora, being these the first report in Argentina for olive trees. P. nicotianae is one of the main responsible of yield losses in woody crops. It is why too much effort has been done to find efficient methods of control, with a low negative impact on environment and to avoid resistant strains selection. In this regard, treatment with phosphites could be a valid strategy. The aim of this work was to determine the fungistatic activity of copper, zinc and potassium phosphites on mycelium growth of P. nicotianae. The effect of phosphites at several concentrations was evaluated in vitro, through the supplemented culture medium technique. The colony diameter was recorded daily. The inhibition percentages were calculated and compared using analysis of variance. An inhibition curve was made and the required concentration to inhibit 50 and 95% of mycelial growth was calculated by non-linear regression. A completed inhibition of the mycelial growth was observed when copper and zinc phosphites were employed at 10 ppm. Copper, zinc and potassium phosphites concentration which inhibit the 50% of the mycelial growth of P. nicotianae was respectively 0.3, 0.6 and 0.7 ppm, whereas for the 95% inhibition was 1.7 ppm for the first two phosphites; unfortunately, the corresponding concentrations for potassium phosphites could not be determined. It is concluded that all these phosphites have inhibited the growth of the mycelium of P. nicotianae and therefore could be considered as a viable alternative for its control.